Targeting the Retinoid X Receptor Pathway Prevents and Ameliorates Murine Chronic Graft-Versus-Host Disease - Thangavelu, Govindarajan; Zaiken, Michael C.; Mohamed, Fathima A.; Flynn, Ryan; Du, Jing; Rhee, Stephanie Y.; Riddle, Megan J.; Aguilar, Ethan G.; Panoskaltsis-Mortari, Angela; Sanders, Martin E.; Blazar, Bruce R. (Frontiers in Immunology, 2022)
Most allogeneic hematopoietic stem cell transplant (allo-HSCT) recipients receive peripheral blood stem cell grafts resulting in a 30%–70% incidence of chronic graft-versus-host disease (cGVHD), a major cause of mortality and morbidity in long-term survivors. While systemic steroids remain the standard of care for first-line therapy, patients may require long-term administration, and those with steroid-resistant or refractory cGVHD have a worse prognosis. Although durable and deep responses with second-line therapies can be achieved in some patients, there remains an urgent need for new therapies. In this study, we evaluated the efficacy of IRX4204, a novel agonist that activates RXRs and is in clinical trials for cancer treatment to prevent and treat cGVHD in two complementary murine models. In a major histocompatibility complex mismatched, non-sclerodermatous multiorgan system model with bronchiolitis obliterans, IRX4204 prevented and reversed cGVHD including associated pulmonary dysfunction with restoration of germinal center T-follicular helper: T-follicular regulatory cell balance. In a minor histocompatibility antigen disparate sclerodermatous model, IRX4204 treatment significantly prevented and ameliorated skin cGVHD by reducing Th1 and Th17 differentiation due to anti-inflammatory properties. Together, these results indicate that IRX4204 is a promising therapeutic option to treat cGVHD with bronchiolitis obliterans or sclerodermatous manifestations.